Paneth cell development in the neonatal gut: pathway regulation, development, and relevance to necrotizing enterocolitis - Yang, Jiahui; Shi, Yongyan (Frontiers in Cell and Developmental Biology, 2023)
Paneth cells (PCs) are intestinal epithelial cells (IECs) that contain eosinophilic granules, which are located in Lieberkühn crypts. An increasing number of animal and human experiments have indicated that PCs are involved in the progression of a variety of intestinal as well as systemic inflammatory responses including necrotizing enterocolitis (NEC). NEC is an enteric acquired disease with high mortality that usually occurs in premature infants and neonates, however the underlying mechanisms remain unclear. In this review, we summarize the features of PCs, including their immune function, association with gut microbiota and intestinal stem cells, and their mechanism of regulating IEC death to explore the possible mechanisms by which PCs affect NEC.